Acessibilidade e resolutividade em assistência oftalmológica para o SUS - Satto, Larissa Horikawa [UNESP] (2015)
Objective: the main goal is to determine if a mobile eye clinic can be used to improve access to eye care. Furthermore is shown the individual profiles that need ophthalmic examination, the main ocular diseases and the treatments necessary to solve the problems. Methods: a cross sectional survey was conduct in fourteen cities of middle-west region of São Paulo St/Brazil, in localities which requested the service provided by the mobile ophthalmic unit. The sample was intentional, the participants were of Brazilian Unified Health System users, who spontaneously search for eye care. Both men and women were eligible, without restrictions about age or socioeconomical status. The data were transferred to Excel Table and statistical analysis was performed. Results: A total of 6878 people participated in this study, 65.54% were female. The mean age was 44 years old (range 4 months to 96 years). The most common ocular complaints were near visual difficulty (60.35%), followed by visual difficulty for distance (55.99%) and headache (26.69%). The main diagnosis was refractive errors (78.60%), followed by cataract (9.60%) and pterygium (8.31%). Spectacles was prescribed to 60% and was maintained to 10%, and for about 28%, only orientation was necessary. 18.10% of the sample were referred to the Ophthalmology Service of Botucatu Medical School, highlighting the cases of oculoplastic surgery (36.14%) and cataract (31.80%). The prevalence of low vision and blindness and the prescribed treatment were similar in both cities with or without ophthalmologist, the need for referral to a tertiary center was highter for patients who live in cities with ophthalmologist. Conclusion: the most common problem for patients from the Brazilian Unified Health System who sought for eye care was the need of spectacles prescription. Mobile eye clinic has a high degree of resoluteness for eye problems, with a small percentage in need to referrals to tertiary service, ...